Cultivating Self-Acceptance: A Study on the Effectiveness of Acceptance and Commitment Therapy (ACT) in the ODHIV Community - Sutansyah, Sani; Wibhowo, Christin; Siswanto, Siswanto (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
People with HIV/AIDS (PWHA), particularly from the Men who have Sex with Men (MSM) group, often face double stigma which negatively impacts their self-acceptance. Low self-acceptance can hinder treatment adherence and quality of life. Acceptance and Commitment Therapy (ACT) is a psychotherapeutic approach hypothesized to improve self-acceptance. This study aimed to examine the effectiveness of Acceptance and Commitment Therapy (ACT) intervention in improving self-acceptance among PWHA from the MSM group. The study used a one group pre-test post-test design. Participants were five MSM PWHA selected by purposive sampling. The ACT intervention was delivered in six individual sessions. The measurement instrument used was the Unconditional Self-Acceptance Questionnaire (USAQ). Data were analyzed statistically using the Wilcoxon Signed Rank Test and supported by qualitative analysis from observations and interviews. The statistical test results showed a significant increase (Z = -2.032; p = 0.042) between the pre-test scores (Mean = 33.8; low category) and post-test scores (Mean = 57.2; moderate category). Qualitatively, participants reported reduced anxiety and negative thoughts, as well as an increased ability to accept their condition and openness to socialize. Although significant, no participant reached a "high" level of self-acceptance. Acceptance and Commitment Therapy (ACT) was proven effective in improving self-acceptance among MSM PWHA, although the achieved improvement has not yet reached an optimal level. Long-term intervention or a combination with other approaches is recommended to strengthen the outcomes.Orang dengan HIV/AIDS (ODHIV), khususnya dari kelompok Laki-laki Seks Laki-laki (LSL), sering menghadapi stigma ganda yang berdampak buruk pada penerimaan diri. Penerimaan diri yang rendah dapat menghambat kepatuhan pengobatan dan kualitas hidup. Acceptance and Commitment Therapy (ACT) merupakan pendekatan psikoterapi yang dihipotesiskan dapat meningkatkan penerimaan diri. Penelitian ini bertujuan untuk menguji efektivitas intervensi Acceptance and Commitment Therapy (ACT) dalam meningkatkan penerimaan diri pada ODHIV kelompok LSL. Penelitian menggunakan desain one group pre-test post-test. Partisipan berjumlah lima orang ODHIV LSL yang dipilih melalui purposive sampling. Intervensi ACT diberikan dalam enam sesi individu. Instrumen pengukuran menggunakan Unconditional Self-Acceptance Questionnaire (USAQ). Data dianalisis secara statistik menggunakan Wilcoxon Signed Rank Test. Hasil uji statistik menunjukkan peningkatan yang signifikan (Z = -2,032; p = 0,042) antara skor pre-test (Mean = 33,8; kategori rendah) dan post-test (Mean = 57,2; kategori sedang). Secara kualitatif, partisipan melaporkan penurunan kecemasan, pikiran negatif, serta peningkatan kemampuan untuk menerima kondisi dan keterbukaan untuk bersosialisasi. Meskipun signifikan, tidak ada partisipan yang mencapai tingkat penerimaan diri "tinggi". Acceptance and Commitment Therapy (ACT) terbukti efektif dalam meningkatkan penerimaan diri pada ODHIV LSL, meskipun peningkatan yang dicapai belum mencapai tingkat optimal. Disarankan intervensi jangka panjang atau kombinasi dengan pendekatan lain untuk memperkuat hasil.